Public and Private Welfare in Modern Europe Productive Entanglements - Giomi, Fabio; Keren, Célia; Labbé, Morgane (Routledge Open History, 2022)
Since the 1980s, neoliberals have openly contested the idea that the state should protect the socio-economic well-being of its citizens, making 'privatization' their mantra. Yet, as historians and social scientists have shown, welfare has always been a 'mixed economy', wherein private and public actors dynamically interacted, collaborating or competing with each other in the provision of welfare services. This book will be of interest to students, scholars and practitioners of welfare by developing three innovative approaches. Firstly, it　illuminates the productive nature of public/private entanglements. Far from amounting to a zero-sum game, the interactions between the two sectors have changed over time what welfare encompasses, its contents and targets, often engendering the creation of new fields of intervention. Secondly, this book departs from a well-established tradition of comparison between Western nation-states by using and mixing various scales of analysis (local, national, international and global) and by covering case studies from Spain to Poland and France to Greece in the nineteenth and twentieth centuries. Thirdly, this book goes beyond state centrism in welfare studies by bringing back a host of public and private actors, from municipalities to international organizations, from older charities to modern NGOs.